Design and Fabrication of low capacity Torque Transducer. Issue 1 (February 2020) - Yadav, Pooja; Pant, Meena; Sheoran, Ankita; Kumar Arora, Pawan; Kumar, Harish
Abstract: The current work focuses on the development of a Torque Transducer capability of 10 Nm and analysis of it using FEA software ABQUS V.2018, it also focuses on identification of important parameters that impacts the stress values like mesh type and global seed size, values of stresses obtained using both analytically and computational are compared and parameters for which most conforming results are obtained is identified. Effect of mesh size and type has been thoroughly studied and it is analyzed what mesh type and what mesh size gives results most closer to analytical values. Using the same analysis it is found out at what point maximum stress, strain values occur on the surface, this helps in ascertaining the locations where strain gauges could be mounted on the sensing elements. For analysis purpose model is prepared using Autodesk Fusion 360 software and on that FEA is performed. Further the designed model has been fabricated using series of CNC machining operations After the fabrication is complete, strain gauges are mounted on previously identified location to measure the strain / stress values.